Association of mitochondrial DNA copy number with metabolic syndrome and type 2 diabetes in 14 176 individuals. (20th February 2021) - Fazzini, F.; Lamina, C.; Raftopoulou, A.; Koller, A.; Fuchsberger, C.; Pattaro, C.; Del Greco, F. M.; Döttelmayer, P.; Fendt, L.; Fritz, J.; Meiselbach, H.; Schönherr, S.; et al.
Abstract: Background: Mitochondria play an important role in cellular metabolism, and their dysfunction is postulated to be involved in metabolic disturbances. Mitochondrial DNA is present in multiple copies per cell. The quantification of mitochondrial DNA copy number (mtDNA‐CN) might be used to assess mitochondrial dysfunction. Objectives: We aimed to investigate the cross‐sectional association of mtDNA‐CN with type 2 diabetes and the potential mediating role of metabolic syndrome. Methods: We examined 4812 patients from the German Chronic Kidney Disease (GCKD) study and 9364 individuals from the Cooperative Health Research in South Tyrol (CHRIS) study. MtDNA‐CN was measured in whole blood using a plasmid‐normalized qPCR‐based assay. Results: In both studies, mtDNA‐CN showed a significant correlation with most metabolic syndrome parameters: mtDNA‐CN decreased with increasing number of metabolic syndrome components. Furthermore, individuals with low mtDNA‐CN had significantly higher odds of metabolic syndrome (OR = 1.025; 95% CI = 1.011–1.039, P  = 3.19 × 10 −4, for each decrease of 10 mtDNA copies) and type 2 diabetes (OR = 1.027; 95% CI = 1.012–1.041; P  = 2.84 × 10 −4 ) in a model adjusted for age, sex, smoking and kidney function in the meta‐analysis of both studies. Mediation analysis revealed that the association of mtDNA‐CN with type 2 diabetes was mainly mediated by waist circumference in the GCKD study (66%) and by several metabolic syndrome parameters, especially body mass index and triglycerides, in the CHRIS study (41%). Conclusions: Our data show an inverse association of mtDNA‐CN with higher risk of metabolic syndrome and type 2 diabetes. A major part of the total effect of mtDNA‐CN on type 2 diabetes is mediated by obesity parameters. Abstract :